Exploring Learning Ownership and Learning Traditions of Pre-Service Teachers During Teaching Internship - Antonio, Marites; Fitrah, Yundi; Kusmana, Ade; Wulandari, Bunga Ayu (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2024)
The teaching Internship Program is the culmination of all the theoretical knowledge gained from the academe and its application to natural settings of education. Its success accurately measures pre-service teachers' competencies and the relevance and effectiveness of teacher education curricula. However, there is a difference between the learning experiences in the academe and those in the actual classroom environment. This study explored the meaningful learning experiences of the pre-service teachers through their narrative reflections. This study used a qualitative research design to investigate the emphasis in the teaching internship experiences on learning ownership and learning trajectory of the forty-four (44) Bachelor of Elementary Education (BEED) pre-service teachers during the teaching internship program. The participants' narrative reflections are the data for the study. Thematic analysis was used to analyze the data. The results revealed solid evidence of the participants' ownership of learning: understanding learners, teachers' professional identities, and self-proclaimed perspectives in teaching. There is also a trend in the learning trajectory characterized by different phases of learning demonstrated among the participants as time progressed during the internship.